Metabolic syndrome and smoking are associated with an increased risk of nocturia in male patients with benign prostatic enlargement. Issue 2 (June 2018) - Nunzio, Cosimo; Brassetti, Aldo; Proietti, Flavia; Deroma, Marianna; Esperto, Francesco; Tubaro, Andrea
Abstract Background To evaluate the relationship between cigarette smoking, metabolic syndrome (MetS) and nocturia in patients with lower urinary tract symptoms (LUTS) and benign prostatic enlargement (BPE). Methods From 2009 onward, a consecutive series of patients with LUTS/BPE were enrolled. Symptoms were assessed using the International Prostate Symptom Score (IPSS). Age, body mass index (BMI), smoker status, prostate volume (PV), prostate-specific antigen (PSA) levels, fasting glucose levels, triglyceride levels, and high-density lipoprotein levels were recorded. MetS was defined according to Adult Treatment Panel III criteria. Moderate/severe nocturia was defined as nocturnal micturition episodes ≥2. Results Overall 492 patients were enrolled with median age and BMI of 68 years (IQR 61/74) and 26.5 kg/m2 (IQR: 24/29), respectively. Moderate/severe nocturia was reported in 212 (43.1%) patients. MetS was diagnosed in 147 (29.9%) patients and out of them 89 (60.5%) complained moderate/severe nocturia (p = 0.001). Overall 187 (38%) patients were current smokers and out of them 99 (52%) presented moderate/severe nocturia(p = 0.034). Patients with moderate/severe nocturia were older (p = 0.001) and with larger prostate volume (p = 0.003). On multivariate analysis, age (OR: 1.067 per year, 95% CI: 1.036–1.098;p = 0.001), PV (OR: 1.011 per ml, 95% CI: 1.003–1.019;p = 0.006), MetS (OR: 2.509, 95% CI: 1.571–4.007;p = 0.001) and smoking (OR: 1.690, 95% CI: 1.061–2.693;p = 0.027) were associated with nocturia severity. Conclusions MetS and smoking doubled the risk of moderate/severe nocturia in patients with LUTS and BPE. Assessing smoking and metabolic status in LUTS/ BPE patients is suggested.